Efficacy of continuing anti-angiogenic agents in the second-line treatment for metastatic colon cancer depending on the KRAS mutation status: a meta-analysis - M. Yu. Fedyanin; A. A. Tryakin; S. A. Tjulandin (Тазовая хирургия и онкология, 2018)
Objective: to assess the efficacy of anti-angiogenic agents incorporated into second-line chemotherapeutic regimens for metastatic colon cancer depending on the KRAS gene mutation status.Materials and methods. We selected completed prospective randomized controlled phase III clinical trials evaluating the efficacy of antiangiogenic agents (bevacizumab, ramucirumab and aflibercept) added to second-line chemotherapy for metastatic colon cancer with subanalysis of treatment efficacy depending on the KRAS gene mutation status. Meta-analysis was performed using the ReviewManager (RevMan) v. 5.3 (The Cochrane Collaboration, Denmark).Results. Three studies (ML18147, RAISE, VELOUR) involving 2165 patients (1137 with KRAS wild-type tumors and 1028 with KRAS-mutant tumors) met the inclusion criteria and were included into this meta-analysis. The majority of patients (84 %) received bevacizumab in the first-line treatment. The results of our meta-analysis suggest that adding an anti-angiogenic drug to chemotherapy in patients with KRAS wildtype colon cancer significantly improved both progression-free survival (hazard ratio (HR) 0.71; 95 % confidence interval (CI) 0.62–0.80; р <0.00001; I2 = 22 %, p = 0.21) and overall survival (HR 0.76; 95 % CI 0.66–0.88; р = 0.0001; I2 = 0, p = 0.59). In patients with KRASmutant colon cancer, incorporation of an anti-angiogenic drug into the treatment regimen was not associated with better overall survival (ОР 0.9; 95 % CI 0.79–1.03; р = 0.11; I2 = 0, p = 0.98), although improved progression-free survival (HR 0.78; 95 % CI 0.68–0.89; р = 0.0002; I2 = 0, p = 0.46). Conclusion. Continuation of anti-angiogenic therapy in the second-line treatment for metastatic colon cancer is most effective in patients with KRAS wild-type tumors. In individuals with KRAS-mutant tumors, continuation of bevacizumab or switch to another anti-angiogenic agent in the second-line treatment improves progression-free survival and has a statistically insignificant effect on overall survival.